Infinity puzzle - Close, Frank (Oxford: Oxford University Press, 2013)
"Speculation is rife that by 2012 the elusive Higgs boson will be found at the Large Hadron Collider. If found, the Higgs boson would help explain why everything has mass. But there's more at stake-what we're really testing is our capacity to make the universe reasonable. Our best understanding of physics is predicated on something known as quantum field theory. Unfortunately, in its raw form, it doesn't make sense-its outputs are physically impossible infinite percentages when they should be something simpler, like the number 1. The kind of physics that the Higgs boson represents seeks to "renormalize" field theory, forcing equations to provide answers that match what we see in the real world. The Infinity Puzzle is the story of a wild idea on the road to acceptance. Only Close can tell it"--Provided by publisher.
Many mysteries of the atom have came unraveled, but one remains intractable- what Frank Close calls the "Infinity puzzle'. The problem was simple to describe. Although clearly very powerful, quantum field theory was making one utterly ridiculous prediction: that certain events had an infinite probability of occurring. The Infinity Puzzle charts the birth and life of the idea, and the scientists, who realized it. Based on numerous firsthand interviews and extensive research, this book captures an era of great mystery and greater discovery. Even if the Higgs boson is never found, renormalization- the pursuit of an orderly universe- has led to one of the richest and most productive intellectual periods in human history.--[book jacket]
Prologue : Amsterdam, 1971 -- Genesis. The point of infinity ; Shelter Island and QED ; Feynman, Schwinger, --and Tomonaga (and Dyson) ; Intermission : 1950 ; Abdus Salam : a strong beginning ; Yang, Mills, --and Shaw ; The identity of John Ward ; The marriage of weak and electromagnetic forces-- to 1964 ; Intermission : 1960 ; Broken symmetries ; "The boson that has been named after me," a.k.a., the Higgs Boson ; Intermission : mid-1960s ; 1967 : from Kibble to Salam and Weinberg ; "And now I introduce Mr. 't Hooft" ; Intermission : early 1970s -- Revelation. B.J. and the cosmic quarks ; A comedy of errors ; Intermission : 1975 - Heavy light ; Warmly admired, richly deserved ; The big machine ; Intermission : end of the twentieth century ; To infinity and beyond.
Includes bibliographical references and index.
Keywords: Quantum field theory; Higgs bosons; Infinite